The Finds of Golden Horde Coins in India and China - Pachkalov A.V. (Золотоордынское обозрение)
Research objectives: The study of all known Golden Horde coin finds in India and China. Research materials: All the known coin finds of the Golden Horde in India and China in the context of published coin finds (the research of Ch.J. Rodgers, M.A. Stein, and others). Results and novelty of the research: The author, for the first time ever, summarized the information about Golden Horde coin finds from these two countries. All Golden Horde coins from China and a portion of Golden Horde coins from India (Indian museum) were minted in Khwarazm. There is numismatic catalogue of Islamic coins from the Calcutta Museum where it is possible to find information about Golden Horde coins from the collection of the museum. Any information about finds of these coins is absent in this publication. However, it is most probable that these coins were found in India because the numismatic collections of such local museums were created practically only from local finds. The Golden Horde coins from the Calcutta Museum collection are mainly silver dirhams of the fourteenth century from Khwarazm, but there are also several coins from Lower Volga region. Probably, the Golden Horde coins went to India and China via Khwarazm. The materials published in the article gives archaeological evidence about close trade routes between Khwarazm on one end and India and Eastern Turkestan on the other end. The peak activity on these trade routes is dated to the second half of fourteenth century (mainly the coins of Uzbek and Janibek Khan of the Golden Horde). At the end of fourteenth century, the most important cities of the Golden Horde were in decline or ceased to exist as a result of Timur’s campaigns against it. The main trade routes between East and West shifted towards the south and stopped passing through the territory of the Ulus of Jochi. Not a single specimen of the finds is dated to the fifteenth century.